Radiopharmacology: Hazard or/and Benefit - Flemming, K. (Nuklearmedizin - NuclearMedicine, 1984)
In the beginning of medical radiology, only the benefit of ionizing radiation was obvious, and radiation was handled and applied generously. After late effects had become known, the radiation exposure was reduced to doses following which no such effects were found. Thus, it was assumed that one could obtain an optimal medical benefit without inducing any hazard. Later, due to experimental findings, hypotheses arose (linear dose-effect response, no time factor) which led to the opinion that even low and lowest radiation doses were relevant for the induction of late effects. A radiation fear grew, which was unintentionally strengthened by radiation protection decrees: even for low doses a radiation risk could be calculated. Therefore, it was believed that there could still exist a radiation hazard, and the radiation benefit remained in question. If, however, all presently known facts are considered, one must conclude that large radiation doses are hazardous and low doses are inefficient, whereas lowest doses have a biopositive effect. Ionizing radiation, therefore, may cause both, hazard as well as benefit. Which of the two effects prevails is determined by the level of dose.